Innovative Strategy in Fundraising Zakat: Case Study at the National Zakat Amil Agency, Tanah Laut Regency - Mahdi Hidayatullah; Wahidah Wahidah; Rusdiana Rusdiana (Penelitian dan Pengembangan Ilmu, 2024)
This study explores the innovative strategies in zakat fundraising implemented by the National Zakat Board (Badan Amil Zakat Nasional, BAZNAS) in Tanah Laut District. The research focuses on the management of fundraising activities, including planning, strategy selection, marketing, receipt and distribution of funds, stewardship, and reporting. The qualitative approach, through interviews, observations, and documentation, reveals that BAZNAS Tanah Laut has effectively integrated various fundraising strategies to enhance zakat collection and distribution. The organization emphasizes the importance of planning and aligns its fundraising activities with its annual work plan, strategic plan, and annual budget. Innovative marketing techniques, both offline and online, play a crucial role in reaching a wider audience and encouraging zakat payment. The study also highlights the challenges faced in fundraising efforts, such as building trust among potential zakat payers and navigating external obstacles. Despite these challenges, BAZNAS Tanah Laut demonstrates a commitment to transparency, accountability, and effective communication with stakeholders. This research contributes to the understanding of zakat management practices and offers insights for other zakat institutions aiming to improve their fundraising strategies.